PENERAPAN KAIDAH FIQHIYYAH AL-DHARARU YUZAL - PANE, ISMAIL; M RIDHO RAMADHANI; TUTUT SARTIKA SIREGAR; AKMAL ABDUL MUNIR; ASLATI (Jurnal Payung Sekaki : Kajian Keislaman, 2024)
Solving problems using the rules of fiqhiyyah, and showing that the rules of fiqhiyyah is one of the disciplines, does not stand alone in its themes and studies. As a derivation of jurisprudence or Islamic law, the rules of fiqhiyyah are common nodes of some problems of Islamic law that can be used by laypeople and fuqaha in finding solutions to legal problems that arise in the community in various themes both worship, muamalah, and contemporary Islamic legal issues. This study aims to determine the application of the rules of fiqhiyyah Al-Dhararu Yuzal in solving problems of Islamic law. The method used in this study is the SLR (Systematic Literature Review) method. The result and Conclusion is that the rule of Al-Dhararu Yuzal (الضرر يزال) is one of the five qawaid fiqhiyyah kulliyah kubra, and has several branch rules.